The Togutil Tribe In The Development Of The Masses Today - Bahrudin Hasan (International Journal of Education, Information Technology, and Others, 2026)
The purpose of this research is to find out how the Togwil tribe developed, the history of the existence of the Togutil tribe, understand their lives and how they survive in the midst of the development of the modern era today. The research approach used is qualitative research, which seeks to understand and explain the history of the existence of the Togutil tribe in the East Halmahera region, the cultural changes that occurred to them and how the Togutil people live today. The results of the study show that the Togutil people in the eastern Halmahera area are mostly from the Tidore tribe due to the occurrence of mass colonialism and the political turmoil of the colonizer masses, the cultural changes that occur in the midst of the Togutil tribe are caused by continuous interaction with local residents, traditional leaders, community leaders, religious leaders so as to create awareness of their lives that are very backward Far from the surrounding community, this awareness then changes the patterns of piker, attitudes and behaviors in their lives, which are better than before